Study on passivation mechanism of HRB500E rebar in highly alkaline concrete pore solution - Zeyun Zeng; Jingtian You; Shangjun Gu; Jie Wang; Fulong Wei; Xiang Xie; Zhiying Li; Hui Yang; Changrong Li (Scientific Reports)
Abstract This study comprehensively investigates the passivation mechanism of HRB500E rebar in highly alkaline concrete pore solution by examining phase transformation thermodynamics, microstructural characteristics, and electronic properties, combined with passivation experiments. The results demonstrated that the microcell models exhibited three distinct passivation behaviors in the initial stage of passivation. Firstly, the certain inclusions/second-phase precipitates with smallest work functions underwent the preferential dissolution, exhibiting the following pitting susceptibility tendency: TiVN2 > Ca8MgAl6Si5O28 > NbVCN > MnS > TiN. Secondly, SiO2, CaAl2SiO6 and CaMgSiO4 with higher work function served as cathodes, while the surrounding matrix functioned as anodes and underwent the rapid dissolution. Subsequently, the surface of rebar formed the polygonal passivation products, and gradually overlapping and covering the inclusions. Finally, the lamellar cementite, exhibiting the smallest work function, underwent the anodic dissolution. These findings indicated that the full passivation on the surface of rebar was developed through matrix dissolution induced by inclusions/second-phase precipitates, ultimately resulting in the nano-particle products aggregated into a continuous passivation film.